Survival Analysis of Industrial Sectors in Indonesia Companies - Farida Titik Kristanti; Deannes Isnuwardhana (University of Merdeka Malang, 2018)
The objective of this study is to discover evidence whether the variables selected as predictors affect the probability of companies experiencing financial distress. Through a purposive sampling technique, 336 companies listed on the Indonesia Stock Exchange were chosen and then grouped into three sectoral groups of companies. One of evidence resulted from survival analysis using the Cox hazard model showed that if the control of corruption increases then the probability of companies undergoing financial distress will decrease. During the research, the evidence was consistent across the three sectoral groups of Infrastructure, Mining, Property (IMP); Basic industry and chemical, Consumer goods industry, Miscellaneous (BCM); and Agriculture, Trade, and Investment (AT). Results of the study also showed that the companies, on the average, had implemented good corporate governance. It could be seen from the percentage of the independent commissioner involvement, which exceeded the minimum requirement of 30 percent as stated in its regulation. Among the groups, IMP had the highest average of leverage, operational risk, and size, but contrastively it had the lowest average of profitability. The results of this study can be used by the government to further improve the control of corruption in order to prevent companies from experiencing financial distress. Meanwhile, companies should not also do something encouraging bureaucrats to corrupt.JEL Classification: G33, G34DOI: https://doi.org/10.26905/jkdp.v22i1.1601